The Phylogenetic Distribution of Non-CTCF Insulator Proteins Is Limited to Insects and Reveals that BEAF-32 Is Drosophila Lineage Specific. - Schoborg, T.A.; Labrador, M. (Journal of Molecular Evolution, 2010)
Chromatin insulators are DNA sequences found in eukaryotes that may organize genomes into chromatin domains by blocking enhancer-promoter interactions and preventing heterochromatin spreading. Considering that insulators play important roles in organizing higher order chromatin structure and modulating gene expression, very little is known about their phylogenetic distribution. To date, six insulators and their associated proteins have been characterized, including Su(Hw), Zw5, CTCF, GAF, Mod(mdg4), and BEAF-32. However, all insulator proteins, with the exception of CTCF, which has also been identified in vertebrates and worms, have been exclusively described in Drosophila melanogaster. In this work, we have performed database searches utilizing each D. melanogaster insulator protein as a query to find orthologs in other organisms, revealing that except for CTCF all known insulator proteins are restricted to insects. In particular, the boundary element-associated factor of 32 kDa (BEAF-32), which binds to thousands of sites throughout the genome, was only found in the Drosophila lineage. Accordingly, we also found a significant bias of BEAF-32 binding sites in relation to transcription start sites (TSSs) in D. melanogaster but not in Anopheles gambiae, Apis mellifera, or Tribolium castaneum. These data suggest that DNA binding proteins such as BEAF-32 may have a dramatic impact in the genome of single evolutionary lineages. A more thorough evaluation of the phylogenetic distribution of insulator proteins will allow for a better understanding of whether the mechanism by which these proteins exert their function is conserved across phyla and their impact in genome evolution.